Efektivitas Manajemen Sumber Daya Manusia Untuk Pengelolaan Industri Berbasis Ekonomi Kreatif di SK COFFEE LAB Kediri - Ainun Muhtadin; Aniza Chairani; Ichwan Setiarso; Widyatmoko Widyatmoko (Universitas Dian Nuswantoro, 2022)
The purpose of this study is to provide exposure by processing and reviewing to be able to find out more deeply about the effectiveness of human resource management regarding the relationship between creative economy management. Effectiveness measures the achievement of the goals to be achieved by the level of success produced by a person or organization. Therefore, the level of the plan achieved can be more effective through the management of Human Resource Management (HR) as one of the most important elements in moving the creative Economic Industry sector so that it can continue to run. The research method uses qualitative research methods, namely research by, analyzing and making data interventions found based on the results of interviews, observations (observations) and document studies. HR management has a role to regulate the management of existing human resources and natural resources, namely the workforce so that they can provide maximum results in order to achieve goals and objectives. The creative economy relies on the capabilities possessed to be concentrated in existing problems, to be able to obtain results from processing sources of knowledge, information possessed and the creativity that exists to support the development of various sectors of the creative economy.